Bacterial symbiosis in Bactrocera oleae, an Achilles' heel for its pest control. (21st July 2020) - Bigiotti, Gaia; Sacchetti, Patrizia; Pastorelli, Roberta; Lauzon, Carol R.; Belcari, Antonio
Abstract: Investigations on microbial symbioses in Tephritidae have increased over the past 30 years owing to the potential use of these relationships in developing new control strategies for economically important fruit flies. Bactrocera oleae (Rossi)—the olive fruit fly—is a monophagous species strictly associated with the olive tree, and among all the tephritids, its symbionts are the most investigated. The bacterium Candidatus Erwinia dacicola is the major persistent resident endosymbiont in wild B. oleae populations. Its relationship with B. oleae has been investigated since being identified in 2005. This endosymbiont is vertically transmitted through generations from the female to the egg. It exists at every developmental stage, although it is more abundant in larvae and ovipositing females, and is necessary for both larvae and adults. Studying B. oleae–Ca . E. dacicola, or other B. oleae –microbe interactions, will allow us to develop modern biological control systems for area‐wide olive protection and set an example for similar programs in other important food crops. This review summarizes the information available on tephritid–microbe interactions and investigates relationships among fruit flies, bacteria and host plants; however, its focus is on B. oleae and its strict association with Ca . E. dacicola to promote environmentally friendly control strategies for area‐wide pest management. Abstract : Investigations on microbial symbioses in Tephritidae have increased over the past 30 years owing to the potential use of these relationships in developing new control strategies for economically important fruit flies. Bactrocera oleae (Rossi)—the olive fruit fly—is a monophagous species strictly associated with the olive tree, and among all the tephritids, its symbionts are the most investigated. The bacterium Candidatus Erwinia dacicola is the major persistent resident endosymbiont in wild B. oleae populations. Its relationship with B. oleae has been investigated since being identified in 2005. This endosymbiont is vertically transmitted through generations from the female to the egg. It exists at every developmental stage, although it is more abundant in larvae and ovipositing females, and is necessary for both larvae and adults. Studying B. oleae–Ca . E. dacicola, or other B. oleae –microbe interactions, will allow us to develop modern biological control systems for area‐wide olive protection and set an example for similar programs in other important food crops. This review summarizes the information available on tephritid–microbe interactions and investigates relationships among fruit flies, bacteria and host plants; however, its focus is on B. oleae and its strict association with Ca . E. dacicola to promote environmentally friendly control strategies for area‐wide pest management.